Glucocorticoids Inhibit Plasminogen Activator Production by Endothelial Cells - Laug, Walter E (Thrombosis and Haemostasis, 1983)
Confluent cultures of bovine aortic endothelial cells (BEC) were found to secrete both tissue type plasminogen activator (t- PA) and urokinase type plasminogen activator (u-PA). Exposure of the cultures to increasing concentrations of dexamethasone resulted in a time and concentration dependent inhibition of cellular and secreted u-PA. Complete inhibition of u-PA production and secretion was found at dexamethasone concentrations of 10-8 molar or higher. Several distinct PA forms with molecular weights ranging from 10,000-20,000 to >200,000 were found in the conditioned medium of untreated BEC cultures. After addition of dexamethasone (10-7 molar) to the culture medium the PAs with molecular weights of 117,000, 58,000,47,000, were absent suggesting that they were u-PAs, whereas the PAs with molecular weights of >200,000 and 75,000 remained unchanged suggesting their t-PA origins. The PAs with lower molecular weights of 35,000, 28,000 and 10,000 to 20,000 were most likely generated from the higher molecular weight forms by limited proteolysis since they were absent when the medium was conditioned in the presence of the protease inhibitor Trasylol.The two PA types may therefore be independently regulated in BEC.
Keywords: Endothelial cells; Plasminogen activators; Corticosteroids; Inhibition